PERENCANAAN JARINGAN INTERNET ADSL DI APARTEMEN PURI CASABLANCA - Saragih, Hoga; Ali, Mohamad (Teknik dan Ilmu Komputer, 2012)
The world of telecommunications continues to experience growth and development, both from the improvement of peoples needs and increasing demand for telecommunications services and also technology demands on the use of the system with greater capabilities and integrated with the speed that can deliver a higher bit rate for internet service. Puri Casablanca Apartment is a dwelling that is not only occupied by local residents but also by foreigners, where the Internet becomes a necessity. It is necessary to optimize the network of existing phone wires to be used also as a network of Internet access using ADSL technology. To get an idea of the performance of the ADSL access network planning is carried out simulations using the software Opnet IT Guru Academic Edition.ÃÂ ÃÂ Keyword: internet, jaringan kabel, ADSL, opnet